Surinaams contrast Roofbouw en overleven in een Caraïbische plantagekolonie, 1750-1863 - van Stipriaan, Alex (Caribbean Series, 1993)
In-depth study of the Suriname plantations in the 18th and 19th centuries. Based on archival research in England, Suriname, and the Netherlands, this book focuses on the idea that there existed a precarious balance between super exploitation and survival on the coffee, sugar, and cotton plantations.